Early HIV RNA decay during raltegravir-containing regimens exhibits two distinct subphases (1a and 1b). (28th November 2015) - Andrade, Adriana; Guedj, Jeremie; Rosenkranz, Susan L.; Lu, Darlene; Mellors, John; Kuritzkes, Daniel R.; Perelson, Alan S.; Ribeiro, Ruy M.
Abstract : Background: We analyzed the early kinetics with integrase inhibitor treatment to gain new insights into viral dynamics. Methodology: We analyzed data from 39 HIV-1 infected, treatment-naive, participants: 28 treated with raltegravir (RAL; multiple doses) monotherapy for 9 days, and 11 with RAL 400 mg twice daily and emtricitabine (200 mg daily)/tenofovir disoproxil fumarate (300 mg daily). Plasma HIV-1 RNA was measured frequently; the data was fitted using a mathematical model of viral dynamics distinguishing between infected cells with unintegrated HIV DNA and productively infected cells. Parameters were estimated using mixed-effect models. Results: RAL treatment led to a biphasic viral decline with a rapid first phase (1a) lasting approximately 5 days followed by a slower phase (1b). Phase 1a is attributed to the rapid elimination of productively infected cells. Phase 1b reflects the loss of infected cells with nonintegrated provirus due to cell loss and integration of HIV DNA. The half-lives of productively infected cells and of infected cells that had completed reverse transcription but had not yet integrated HIV DNA were approximately 19 h and between 3.6 and 5.8 days, respectively. The effectiveness of RAL in preventing proviral integration was 94% and 99.7%, for the combination therapy and monotherapy groups, respectively. Conclusion: We found that the first phase of viral decay with RAL therapy was composed of two subphases corresponding to the half-lives of infected cells with integrated proviruses and with unintegrated HIV-DNA. Abstract : Supplemental Digital Content is available in the text